Unintentional injury and its prevention in infant: knowledge and self-reported practices of main caregivers - Ramdzan, Siti Nurkamilla (BioMed Central, 2014)
BACKGROUND: Unintentional injuries are the major cause of morbidity and mortality in infants. Prevention of unintentional injuries has been shown to be effective with education. Understanding the level of knowledge and practices of caregivers in infant safety would be useful to identify gaps for improvement. METHODS: A cross-sectional study was conducted in an urban government health clinic in Malaysia among main caregivers of infants aged 11 to 15 months. Face-to-face interviews were conducted using a semi-structured self-designed questionnaire. Responses to the items were categorised by the percentage of correct answers: poor (<50%), moderate (50% – 70%) and good (>70%). RESULTS: A total of 403 caregivers participated in the study. Of the 21 items in the questionnaire on knowledge, 19 had good-to-moderate responses and two had poor responses. The two items on knowledge with poor responses were on the use of infant walkers (26.8%) and allowing infants on motorcycles as pillion riders (27.3%). Self-reported practice of infant safety was poor. None of the participants followed all 19 safety practices measured. Eight (42.1%) items on self-reported practices had poor responses. The worst three of these were on the use of baby cots (16.4%), avoiding the use of infant walkers (23.8%) and putting infants to sleep in the supine position (25.6%). Better knowledge was associated with self-reported safety practices in infants (p < 0.05). However, knowledge did not correspond to correct practice, particularly on the use of baby cots, infant walkers and sarong cradles. CONCLUSION: Main caregivers’ knowledge on infant safety was good but self-reported practice was poor. Further research in the future is required to identify interventions that target these potentially harmful practices.